2023
DOI: 10.1182/bloodadvances.2022009594
|View full text |Cite
|
Sign up to set email alerts
|

A fixed-duration immunochemotherapy approach in CLL: 5.5-year results from the phase 2 ICLL-07 FILO trial

Abstract: In previously untreated, medically fit patients with chronic lymphocytic leukemia, research is focused on developing fixed-duration strategies to improve long-term outcomes whilst sparing patients from serious toxicities. The ICLL-07 trial evaluated a fixed-duration (15-month) immunochemotherapy approach where, following obinutuzumab-ibrutinib induction for 9 months, patients (n=10) in complete remission (CR) with bone marrow (BM) measurable residual disease (MRD) <0.01% continued only ibrutinib 420 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(122 reference statements)
0
2
0
Order By: Relevance
“… 21 The other study, reported by the French Innovative Leukemia Organization (FILO) group, used 9 months of ibrutinib plus obinutuzumab, followed by 4 cycles of fludarabine, cyclophosphamide, and obinutuzumab in CLL regardless of IGHV status. 22 Both studies demonstrated durable PFS (96%-98% at 3 or 4 years) and high rates of CR (60% in the MD Anderson study) or CR with BM-uMRD (62% in the FILO study). The FILO study also demonstrated that deep response was sustained, an 81% rate of PB-uMRD4 at 5 years.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… 21 The other study, reported by the French Innovative Leukemia Organization (FILO) group, used 9 months of ibrutinib plus obinutuzumab, followed by 4 cycles of fludarabine, cyclophosphamide, and obinutuzumab in CLL regardless of IGHV status. 22 Both studies demonstrated durable PFS (96%-98% at 3 or 4 years) and high rates of CR (60% in the MD Anderson study) or CR with BM-uMRD (62% in the FILO study). The FILO study also demonstrated that deep response was sustained, an 81% rate of PB-uMRD4 at 5 years.…”
Section: Discussionmentioning
confidence: 88%
“…To date, the rates of tMN are similar in our iFCR study (2.4% [2/85]; 5-year median follow-up), the study by Jain et al (2% [1/45]; 3-year median follow-up), 21 and the FILO study (2% [2/115]; 5-year median follow-up). 22 Likewise, a retrospective analysis of 3200 patients with CLL treated with FCR or fludarabine plus cyclophosphamide demonstrated no difference in the incidence of tMN in subgroups divided by ≤6 cycles of FCR. 26 Thus, the number of chemoimmunotherapy cycles added to ibrutinib may not be the most important factor contributing to tMN.…”
Section: Discussionmentioning
confidence: 98%